2014
DOI: 10.1101/012443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The neural correlates of dreaming

Abstract: 2Consciousness never fades during wake. However, if awakened from sleep, sometimes we report dreams and sometimes no experiences. Traditionally, dreaming has been identified with REM sleep, characterized by a wake-like, globally 'activated', high-frequency EEG. However, dreaming also occurs in NREM sleep, characterized by prominent low-frequency activity. This challenges our understanding of the neural correlates of conscious experiences in sleep. Using high-density EEG, we contrasted the presence and absence … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
183
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(199 citation statements)
references
References 69 publications
10
183
3
3
Order By: Relevance
“…Interestingly, Siclari et al (2014) found that DR, considered as conscious experience, was related to increased high-frequency power (18-50 Hz) and reduced low-frequency power (1-12 Hz).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Interestingly, Siclari et al (2014) found that DR, considered as conscious experience, was related to increased high-frequency power (18-50 Hz) and reduced low-frequency power (1-12 Hz).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, some studies reported a relationship between high frequency range (18-50 Hz, i.e., gamma activity) and DR (Siclari et al 2014;Voss et al 2014). In particular, a recent withinsubjects study revealed that brain activity characterized by higher power in high-frequency range is associated to the presence of recall on awakening both during REM and NREM sleep (Siclari et al 2014). Also it was reported that the stimulation on the fronto-temporal area in the gamma band by transcranial direct current stimulation (tDCS) during REM sleep elicits lucid dreams (Voss et al 2014).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…też Voss & Hobson 2015 badali, czy stymulacja elektryczna rejonów czołowo-skroniowych mózgu, które zwykle są deaktywowane podczas snu REM, mogą wywołać świadomość śnienia, czyli świadomość tego, że się śni. Wreszcie, kontrast między śnieniem a jego brakiem podczas tej samej fazy snu może poszerzyć istniejące badania nad neuronowymi korelatami świadomości (Noreika 2009, Siclari 2014.…”
unclassified